On the Incompressible Limit for the Compressible Flows of Liquid Crystals under Strong Stratification on Bounded Domains - Young-Sam Kwon (Abstract and Applied Analysis)
We study the incompressible limit of weak solutions for the compressible flows of liquid crystals under strong stratification on bounded domains.